Objective Measurement of Eyelid Force in Ptosis Versus Controls. Issue 8 (November 2019) - Pillar, Shani; Almog, Yehoshua; Sharon, Tal; Dar, Nimrod; Segal, Ori; Nemet, Arie Y.
Abstract : Abstract: Thorough evaluation of the upper eyelid is essential for diagnosis and management planning in blepharoptosis. In a previous study, our group described a novel force gauge for direct assessment of upper lid force in healthy subjects. In this study, the authors apply the same technique for measuring muscle forces in ptotic eyelids. Patients scheduled to undergo surgical repair of aponeurotic blepharoptosis or dermatochalasis, from July 2017 to August 2018, in a tertiary care medical center, were enrolled in this prospective case series. When the eyelid disorder was unilateral, the normal eye was designated as control. The upward force generated by the eyelid was measured directly using a handheld dynamometer noninvasively attached to the upper eyelid. Measurements were conducted with and without fixation of the frontalis muscle, to differentiate between total lid force, levator force, and frontalis contribution. A total of 56 eyes was included in the study: 34 in the ptosis group, 11 in the dermatochalasis group, and 11 as controls. Both the ptosis group and the dermatochalasis group had significantly lower total muscle force and levator force measurements when compared with control ( P <0.05). Calculated frontalis force contribution to upgaze did not differ significantly between groups. In the control group, calculated frontalis force contribution to upgaze strongly correlated to marginal reflex distance1 (r = 0.75, P = 0.05) In conclusion, the authors present a simple, inexpensive, new portable force gauge for direct eyelid force measurements in eyelid pathologies. Distinct differences between ptotic and healthy eyelids are demonstrated, suggesting potential applications in patient evaluation and management. Abstract : Supplemental Digital Content is available in the text